Prevalence and Associated Factors of Gastro-Esophageal Reflux Disease among a Sample of Undergraduate Medical Students in Baghdad - Abdulwahhab, Sarah H.; Al Hashimi, Ban A.R.; Alkhalidi , Nawal M. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Gastroesophageal reflux disease (GERD) is a commonly prevalent gastrointestinal disorder in adults, it develops when the stomach contents reflux and rise up into the esophagus as a result from lower esophageal sphincter dysfunction. Very few studies on magnitude of GERD in student community have been done. The study aim was conducted to determine the prevalence of GERD among sample of  medical students and the potential risk factors associated with it.Method: A cross sectional descriptive study conducted on a sample of 300 undergraduate students of medical college/Baghdad university from 15th of January -1st of June 2020. All participants answered online questionnaire for GERD symptoms. The questionnaire included demographic data like age, gender, height and weight, lifestyle, and dietary habits. Statistical data were analyzed using the Statistical Package for Social Sciences (SPSS) version 25. Results with a P value of